2021
DOI: 10.3390/biology10020142
|View full text |Cite
|
Sign up to set email alerts
|

A Shorter Equilibration Period Improves Post-Warming Outcomes after Vitrification and in Straw Dilution of In Vitro-Produced Bovine Embryos

Abstract: This study was designed to the optimize vitrification and in-straw warming protocol of in vitro-produced bovine embryos by comparing two different equilibration periods, short equilibrium (SE: 3 min) and long equilibrium (LE: 12 min). Outcomes recorded in vitrified day seven (D7) and day eight (D8) expanded blastocysts were survival and hatching rates, cell counts, apoptosis rate, and gene expression. While survival rates at 3 and 24 h post-warming were reduced (p < 0.05) after vitrification, the hatching r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 52 publications
(104 reference statements)
1
14
0
Order By: Relevance
“…Improved cryosurvival has been associated with more advanced embryonic stages on a given in vitro culture day [36]. In concordance with previous studies conducted in our laboratory [36,37], D7 blastocysts derived from cow oocytes had a significantly higher re-expansion rate than blastocysts vitrified/warmed after 8 days in culture, regardless of the vitrification treatment. In bovine species, early cleavage is associated with better embryo quality and implantation [38][39][40], while the timing of blastocyst formation has been correlated to the in-vitro developmental potential of embryos, assessed by total cell number [39], expression of genes related to embryo quality [41], and pregnancy rates [42].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Improved cryosurvival has been associated with more advanced embryonic stages on a given in vitro culture day [36]. In concordance with previous studies conducted in our laboratory [36,37], D7 blastocysts derived from cow oocytes had a significantly higher re-expansion rate than blastocysts vitrified/warmed after 8 days in culture, regardless of the vitrification treatment. In bovine species, early cleavage is associated with better embryo quality and implantation [38][39][40], while the timing of blastocyst formation has been correlated to the in-vitro developmental potential of embryos, assessed by total cell number [39], expression of genes related to embryo quality [41], and pregnancy rates [42].…”
Section: Discussionsupporting
confidence: 88%
“…Vitrification/warming has been found to have a negative effect on TCN and TE cell numbers [37] and ICM cell number [53,54]. When vitrification media were supplemented with AFPs, Liang et al [30] found a significantly higher TCN in blastocysts vitrified/warmed with AFGP8 supplementation than in the non-supplemented group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In blastocyst vitrification using the OC, changing the CPA exposure time did not affect the clinical and neonatal outcomes of human blastocysts [ 48 ], while increasing the CPA exposure time improved DNA integrity in mouse blastocysts [ 49 ]. Due to the reduced cytotoxicity and osmotic stress, short-term equilibration time improved the re-expansion and hatching rates [ 50 ] and increased the total cell number with a reduced mRNA expression of apoptosis-related genes, such as Bax and Bcl2l1 , in bovine blastocysts [ 51 ]. Although a shorter CPA exposure has been proposed to reduce CPA cytotoxicity [ 31 , 32 , 52 , 53 ], other studies have recommended a longer exposure time for human oocytes using OCs [ 54 , 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…VitTrans is a device that allows field‐warming/dilution and embryo transfer directly to female recipients. Vitrification of IVP day 7 bovine blastocysts using the VitTrans vitrification/warming device and short exposure to the CPA equilibration solution results in post‐warming outcomes comparable to those of fresh non‐vitrified blastocysts (Martinez‐Rodero et al, 2021).…”
Section: Introductionmentioning
confidence: 99%